Physicochemical parameters and volatile composition of cachaça produced in the state of Paraíba, Brasil (Research, Society and Development, 2020)
Cachaça is produced and marketed throughout Brazil to an extent that it has become a symbol of the country. To ensure the safety to consumers, the quality of the beverage must meet the legal standards set by Brazilian law. Nevertheless, reports of inadequacies are still common, and the complexity of its composition requires more detailed studies. This study sought to evaluate the chemical composition of cachaça produced in the state of Paraiba, determine the conformity with the parameters required by legislation, and identify volatile compounds present in these beverages. The cachaça samples were collected from the local commerce in their original packaging and sent to the Laboratório de Análise de Qualidade de Aguardente of the Universidade Federal de Lavras, in Lavras, Minas Gerais, Brazil. The parameters analyzed were those established by Brazilian legislation as indicators of quality. Volatile compounds were identified by mass spectrometry coupled to gas chromatography (GC-MS). Among the 20 samples analyzed, 17 were irregular with respect to at least one of the parameters established by the legislation. The complexity of the volatile composition has been proven by the fact that 57 compounds represented mainly by esters (ethyl decanoate and ethyl dodecanoate) and alcohols (3-methyl-1-butanol) were found.